2014
DOI: 10.1002/bjs.9669
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visual force feedback on tissue handling in minimally invasive surgery

Abstract: The tissue-handling skills of medical students improved significantly when they were given force feedback of their performance. This effect was seen mainly during the knot-tying phase of the suturing task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…These results are in agreement with previous studies of force exertion in suturing and knot-tying in laparoscopic surgery [2,4]. This showed that even though all participants were made aware that knot-tying force was measured, novices still have a tendency to be rougher when cinching knots during vessel ligations.…”
Section: Performance Metricssupporting
confidence: 92%
“…These results are in agreement with previous studies of force exertion in suturing and knot-tying in laparoscopic surgery [2,4]. This showed that even though all participants were made aware that knot-tying force was measured, novices still have a tendency to be rougher when cinching knots during vessel ligations.…”
Section: Performance Metricssupporting
confidence: 92%
“…Besides being a valid metric for skills assessment in surgical tasks, force information in a training setting provides information about the risk of tissue damage due to excessive interaction force [26,35,36]. In both pre-and post-course assessments in this study, it was observed that all participants exceeded the safety thresholds for tissue damage.…”
Section: Portal Force and Torquementioning
confidence: 62%
“…Previous studies show that after training in laparoscopic skills with virtual reality or box trainers, a significant reduction in task time is observed [26,[35][36][37][38][39]. Therefore, task time is often used as a performance parameter to indicate efficient learning.…”
Section: Portal Force and Torquementioning
confidence: 99%
“…82 Minimizing the time delay between the movement and feedback is essential to create realistic instrument movement. 19 17 Hanna et al 15 Horeman et al 18,75,76 Rodrigues et al 12,80 Mean absolute nonzero force Averaged mean absolute force of periods during training in which the force was not 0 Newton Cundy et al 17 Horeman et al 18,20,75 Rodrigues et al 12,80 Wottawa et al 81…”
Section: Differentiating Powermentioning
confidence: 99%
“…On the other hand, haptic cues are essential during surgery to control motor functions and render appropriate tissue handling skills. 11,12 Tissue handling should be gentle during surgery and require little force use, since it causes tissue reaction or even damage and consequently can result in intraoperative errors. 4,13 Better task performance is therefore associated with reduced force application.…”
Section: Introductionmentioning
confidence: 99%